1975
DOI: 10.3758/bf03326822
|View full text |Cite
|
Sign up to set email alerts
|

Visual, tactual, and olfactory deprivation effects on irritable fighting behavior of male hooded rats

Abstract: Pairs of experimentally naive blind, anosmic, tactually deprived, and control male rats were compared on successive exposures to footshock. Analyses of generic fight scores and the component scores, i.e., postures, bites, and movements, revealed significantly less fighting in anosmic pairs and virtually no fighting in tactually deprived pairs. Blind pairs fought comparable to controls. The change in quality of fighting by anosmic pairs over successive sessions suggests that form of attack and defensive posturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The permanency of vibrissal cautery is still an open question and one that may have varying answers depending upon the experimental model. In comparison to other sensory deprivation methods for restraining fighting in rats, only anosmia appears to have a compar-able degree of effect (Alberts and Galef, 1973;Luciano, 1974a;Ghiselli and Thor, 1975). a permanent physiological manipulation may have some unique experimental advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The permanency of vibrissal cautery is still an open question and one that may have varying answers depending upon the experimental model. In comparison to other sensory deprivation methods for restraining fighting in rats, only anosmia appears to have a compar-able degree of effect (Alberts and Galef, 1973;Luciano, 1974a;Ghiselli and Thor, 1975). a permanent physiological manipulation may have some unique experimental advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas blinded rats fought at control levels in a shock situation, anosmic and devibrissaed pairs fought less, and olfactory bulbectomized animals showed an increase in mouse killing (cf. Bugbee & Eichelman, 1972;Ghiselli & Thor, 1975;Thor, 1976). Moreover, it has been demonstrated that shock-induced aggression is separable from territorial aggression in rats in terms of the differential influence of hypothalamic lesions on these two response types (Adams, 1971) and the differing behavioral profiles of intact animals across the two situations (Blanchard, Blanchard, & Takahashi, 1978).…”
Section: University Of Wisconsin-madisonmentioning
confidence: 99%
“…There are studies which support this hypothesis. For example, when a rat was made ataxic following the administration of mescaline it was bitten by its untreated opponent when footshock was delivered, but engaged in upright boxing when tested three days later without the drug with the same opponent [Sbordone, 19761 ; when a rat was paired with a guinea pig and both shocked, the rat began t o bite its head [Ulrich and Azrin, 19621. rats in a shock-elicited aggression situation [Ghiselli and Thor, 1975 ;Sbordone and Garcia, 1977;Ulrich and Azrin, 19621. In each of these studies the victim…”
Section: Scussl Onmentioning
confidence: 99%
“…Since, however, several investigators have shown that tactile [Ghiselli and Thor, 1975;Thor, Ghiselli and Lambelet, 19741 ;olfactory [Ghiselli and Thor, 19751 ;and ultrasonic cues [Ghiselli and LaRiviere, 19771 may play a major role in the aggressive behavior of rats in a shock-elicited aggression situation it is possible that these cues may accompany the specific behaviors described above. Thus, further research needs to be done to determine the relative importance of visual, tactile, olfactory and auditory cues elicited by the victim in determining whether an attacking opponent engages in either biting or boxing behaviors.…”
Section: Scussl Onmentioning
confidence: 99%